Topology of nonstationary attractors in spaces of control processes and synergetic model in flight dynamics - Sparavalo, M.K. (Український математичний журнал, 1995)
We give a definition of nonstationary attractors that can originally exist in spaces of control processes and formulate topological conditions for an arbitrary set to belong to the class of nonstationary attractors. We also present a synergetic model for the ascent of an airplane.